فاعلية برنامج إرشادي إلكتروني في تخفيف حدة التذبذب الفكري لدى عينة من طلاب الجامعة: دراسة تجريبية باستخدام نظام البلاك بورد - اللواج، سطوحي سعد رحيم (جامعة دمنهور - كلية التربية, 2022)
هدف البحث إلى تعرف فاعلية برنامج إرشادي إلكتروني في تخفيف حدة التذبذب الفكري لدى عينة من طلاب كلية التربية، جامعة بيشة، وبلغ عدد الطلاب المشاركين في الدراسة الأساسية (٢٤) طالبا من طلاب المستوى السابع بكلية التربية، وقد تم تقسيمهم إلى (١٢) طالبا يمثلون المجموعة التجريبية تراوحت أعمارهم ما بين (٢٢-٢٣) سنة بمتوسط عمري مقداره (22.3) سنة، وانحراف معياري (0.492) و(١٢) طالبا يمثلون المجموعة الضابطة تراوحت أعمارهم ما بين (٢٢-٢٣) سنة بمتوسط عمري مقداره (22.08) سنة، وانحراف معياري (0.5149)، وطبق عليهم مقياس التذبذب الفكري (إعداد الباحث)، واختبار الذكاء اللفظي (إعداد/ جابر عبد الحميد، محمود عمر (٢٠٠٧) وبعد تحليل البيانات إحصائيا باستخدام برنامج الحزم الإحصائية للعلوم الاجتماعية (spss) الإصدار (25)، أظهرت نتائج البحث وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات القياسين القبلي والبعدي للمجموعة التجريبية في الدرجة الكلية للتذبذب الفكري وفي كل بعد من أبعاده لصالح القياس البعدي، وكذلك وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات المجموعتين التجريبية والضابطة في القياس البعدي في الدرجة الكلية للتذبذب الفكري وفي كل بعد من أبعاده لصالح المجموعة التجريبية، كما أظهرت النتائج أيضا عدم وجود فروق دالة إحصائيا بين متوسطي رتب درجات القياسين البعدي والتتبعي للمجموعة التجريبية في أبعاد التذبذب الفكري والدرجة الكلية. The research aimed to know the effectiveness of an electronic counseling program in alleviating intellectual oscillation among a sample of students of the College of Education, University of Bisha. The experimental group’s ages ranged between (22-23) years, with an average age of (22.33) years, and a standard deviation of (0.4923), and (12) students representing the control group, whose ages ranged between (22-23) years, with an average age of (22.083) years. , standard deviation (0.5149), the intellectual oscillation scale (prepared by the researcher), and the verbal intelligence test (prepared by / Jaber Abdel Hamid, Mahmoud Omar (2007) were applied to them. After analyzing the data statistically using the Statistical Package for Social Sciences (SPSS) version (25), the results of the research showed that there were statistically significant differences at the level (0.01) between the mean ranks of the pre and post measurements of the experimental group in the total degree of intellectual oscillation and in each of its dimensions in favor of the post measurement. There were statistically significant differences at (0.01) between the mean scores of the experimental and control groups in the post measurement in the total score of intellectual oscillation and in each of its dimensional in favor of the experimental group. Moreover, there were no statistically significant differences between the mean scores of the post and follow-up measurements of the experimental group in all dimensions of the intellectual oscillation and the total score.
Keywords: الأمن الإجتماعي -- التعليم الإلكتروني -- المنصات التعليمية -- الفصول الإفتراضية -- الإرشاد النفسي